Effects of Fucoidan Isolated From Laminaria japonica on Immune Response and Gut Microbiota in Cyclophosphamide-Treated Mice - Tang, Yunping; Pu, Qiuyan; Zhao, Qiaoling; Zhou, Yafeng; Jiang, Xiaoxia; Han, Tao (Frontiers in Immunology, 2022)
The effects of Laminaria japonica fucoidan (LF) on immune regulation and intestinal microflora in cyclophosphamide (CTX)-treated mice were investigated in this work. Results indicated that LF significantly enhanced the spleen and thymus indices, promoted spleen lymphocyte and peritoneal macrophages proliferation, and increased the immune-related cytokines production in serum. Moreover, LF could regulate intestinal flora composition, increasing the abundance of Lactobacillaceae and Alistipes, and inhibiting Erysipelotrichia, Turicibacter, Romboutsia, Peptostreptococcaceae, and Faecalibaculum. These results were positively correlated with immune characteristics. Overall, LF could be useful as a new potential strategy to mitigate CTX immunosuppression and intestinal microbiota disorders.